Evaluation of pest management strategies in organic and conventional Taraori Basmati rice (Oryza sativa) farming system - SHARMA, O P; GARG, D K; TRIVEDI, T P; CHAHAR, SATPAL; SINGH, S P (The Indian Journal of Agricultural Sciences, 2011)
Integrated pest management (IPM) strategies based on scientifically proven components in organic fields were found to be more effective and sustainable in comparison to indigenous traditional knowledge (ITK)-based and conventional chemical-based strategies. Significant difference in incidence of key insect pests and diseases showed effectiveness of microbial and botanical pesticides against their target organisms, especially for foliar diseases and leaf folder. The yield data indicated that farmers adopting IPM practices were able to get higher yield and better cost:benefit (C : B) ratio (3.29 tonnes/ha,1 : 4.58 and 3.16 tonnes/ha, 1 : 5.63) in comparison to ITK (3.05 tonnes/ha, 1 : 4.12 and 2.85 tonnes/ha, 1 : 4.36) as well as conventional chemical-based farmers’ practice (3.12 tonnes/ha 1 : 3.83 and 3.09 tonnes/ha, 1 : 4.45) during 2005–06 rainy (kharif) season. Quantification of soil (organic carbon) and environmental benefits and impact of IPM practices were quite encouraging in contrast to conventional farms. The IPM resulted in better conservation of natural enemies as evident from presence of numerous predators and parasitoids, like spiders, crickets (egg predators), damselflies, ants, beetles, wasps and mermithids.